A Human Rights Appraisal of the Limits to Judicial Independence for International Criminal Justice. (27th January 2015) - ALMQVIST, JESSICA
Abstract: The UN Security Council's involvement in the area of international criminal justice raises concerns about judicial independence. Of primary concern in this study is the degree to which this political organ has come to determine and restrict jurisdiction of international criminal tribunals, with the effect of excluding cases involving alleged grave crimes by actors whose presence in situations of which the Council is seized is supported by its permanent members. This control, it will be argued, undermines the basic conditions for a sound administration of justice, as it impedes these tribunals from selecting the cases that may come before them in accordance with respect for human rights and the rule of law. More specifically, restrictions imposed by political organs, leading to unjustified unequal treatment before the law and the courts of perpetrators and victims of grave crime in a given situation, are contrary to principles of equality and non-discrimination. A theory of international judicial independence should therefore extend to a consideration of the legality of such restrictions and acknowledge it as an essential requirement of independence.